Kaji Eksperimen Konversi Sepeda Motor Beat 110cc Menjadi Sepeda Motor Plug-in Hybrid - Hari Budianto; Yanto; Arka Dwinanda Soewono (Cylinder : Jurnal Ilmiah Teknik Mesin, 2026)
The conversion of Internal Combustion Engine (ICE) motorcycles into plug-in hybrids is a practical solution for improving fuel efficiency and reducing exhaust emissions in two-wheeled vehicles. This study aims to present the design of an electric motor powertrain for plug-in hybrids, as well as to measure fuel efficiency and estimate the potential annual reduction in CO₂ emissions. Fuel efficiency testing was conducted through an on-road test using an urban driving scenario. The results showed that converting a 2018 Honda Beat motorcycle to a plug-in hybrid improved fuel efficiency by 21.4%, as indicated by an increased travel distance of 36 km. This improvement in fuel efficiency has the potential to reduce CO₂ emissions by 110.1 kg per year for a single converted motorcycle. Currently, the cost of converting a motorcycle to a plug-in hybrid is IDR 15,950,000. This cost is still higher compared to the incentives currently available from the government, making it a major obstacle in attracting public interest.